Hubungan Bayi Berat Lahir Rendah dengan Kejadian Asfiksia Neonatorum di RSUD Dr. Iskak Tulungagung: The Relationship of Low Birth Weight Babies with Asphyxia Neonatorum Incidence in RSUD Dr. Isaac Tulungagung - Astutik, Reni Yuli; Ferawati, Nency (Jurnal Kebidanan Midwiferia, 2018)
Birth weight is one factor of neonates that can cause asphyxia neonatorum and is one indicator ofthe health of the newborn. The result of Riskesdas 2013 explained the low birth weight infants is 10.2% and WHO data shows every year about 3% of 120 million newborn have asphyxia. This study aims to analyze the correlation of low birth weight infants with neonatorum asphyxia incidence in dr. Iskak Tulungagung Hospital year 2016. This study was executed on July 18 to 19 2017 in dr.Iskak Tulungagung Hospital. The type research used analytical survey with correlational design and retrospective cohort study. Independent variable was low birth weight infants and dependent variable was neonatorum asphyxia. The population was 949 and sample was 162 with Simple Random Sampling technique, and used medical record instruments. From the 162 samples, found that almost half of respondents were 46.9% experienced low birth weight infants and almost all of the respondents were 88.3% experienced asphyxia neonatorum. Based on chi square test obtained (p)=0.001<(α)=0,05 and C=0,257, it means there is significant correlation between low birth weight infants and asphyxia with low correlation neonatorum. Odds ratio is 9,116, it means that risk of asphyxia neonatorum at low birth weight infants is 9.116 times great than normal birth weight infant. At the low birth weight infants a lot of risk of problems in the body because immaturity of organ system, so easily attacked by complications such as an asphyxia neonatorum.